Factors Affecting Customer Decision Making on “Chapter” E-Publication Purchase in Thailand - Kunamart, Thitaporn; Methavasaraphak, Preecha (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
While physical book industry is declining, E-Publication industry is developing. New format of E-Publication is out in the form of Chapter E-Publication. However, with limited capital, it should be considered whether investing in Chapter E-Publication platform would be wiser, or other traditional platforms should be pursued. This research aimed to discover the factors affecting customer decision making on Chapter E-Publication, as well as whether customers would considered repurchase the same story in different formats in Thailand. Using quantitative surveys from 396 respondents who experienced purchasing Chapter E-Publication who lived in Thailand, descriptive, correlation, and regression analyses were done. From the analysis, the researcher found that there were five factors that affected the purchase decision of Chapter E-Publication, which are Price, Perceived Ease of Use, Customer Review, Trust, and Perceived Usefulness, respectively. The result could be explained that 71.2% (R2 = .712) of the variation affect in purchase decision of the Chapter E-Publication. In addition, people also had tendency to purchase another format of the publication for the collection purpose. Few recommendations were made for publisher and platform owners to take into consideration for way to survive and maintain long-term sustainability with the customers.